1997
DOI: 10.1046/j.1365-3083.1997.d01-408.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Amyloid A Precursor Protein SAA by Macrophage Cell Lines Obtained from Amyloid Resistant and Susceptible Strains of Mice

Abstract: 1997;45:354-360 Reactive AA amyloidosis can be induced in mice in a model of sustained inflammation following daily casein subcutaneous injections. However, the development of AA amyloidosis is known to vary in different strains of mice. The C57BL/6 strain is susceptible to the development of amyloidosis while the A/J strain is resistant. The degradation of purified serum amyloid A (SAA) protein by human monocytes as well as by mouse macrophages has been shown. The resistance/susceptibility of different mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…In contrast, the SAA-degradative capacity of mØ obtained from mice undergoing an amyloidosis induction protocol showed no difference from that of mØ obtained from healthy control animals [20]. Although it appears that the degradative capacity of mØ is influenced by their orgin and not by the amyloid induction protocol, neither of the two studies investigated the pathway by which SAA was degraded and whether mØ from C57BL/6 and A/J mice apply different pathways to degrade SAA [18,20].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, the SAA-degradative capacity of mØ obtained from mice undergoing an amyloidosis induction protocol showed no difference from that of mØ obtained from healthy control animals [20]. Although it appears that the degradative capacity of mØ is influenced by their orgin and not by the amyloid induction protocol, neither of the two studies investigated the pathway by which SAA was degraded and whether mØ from C57BL/6 and A/J mice apply different pathways to degrade SAA [18,20].…”
Section: Discussionmentioning
confidence: 89%
“…In this respect, quantitative rather than qualitative differences may need to be demonstrated. Ham et al [18] have found that mØ obtained from C57BL/6 mice, in contrast to those obtained from A/J mice, show an intermittent block in the degradation of SAA as analyzed by in vitro degradation experiments with HDL SAA . In contrast, the SAA-degradative capacity of mØ obtained from mice undergoing an amyloidosis induction protocol showed no difference from that of mØ obtained from healthy control animals [20].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the up-regulation of hepatic release of SAA induced as part of a systemic acutephase response may increase levels of plasma SAA available to bind to cells/matrix within the developing granulomatous inflammation. Third, IFN-g directly impairs the degradation of SAA by macrophages, which would enhance local accumulation and persistence of SAA (26). Although the dominant mechanism(s) remain unknown, we posit that the actual level of SAA up-regulation is not as critical as the factors that lead to aggregation and persistence of SAA (both nonfibrillar and fibrillar forms) that promotes further accumulation of SAA within the sarcoidosis granulomas.…”
Section: Discussionmentioning
confidence: 96%
“…CD3 1 T cells could also regulate trafficking of SAA-expressing inflammatory cells to sites of granulomatous inflammation. Importantly, IFN-g has been shown to directly impair the degradation of SAA by macrophages favoring extracellular accumulation and fibril formation (26), an effect that can directly link Th1 responses to enhanced aggregation and persistence of SAA. Together, these histopathologic observations provide the spatial context for the hypothesis that SAA is a bridge between the innate and adaptive immune responses that determine a specific pathobiologic development of granulomatous inflammation in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…It may be degraded completely without the occurrence of fragments [13,38,64] or incompletely with the generation of fragments resembling the AA fibril proteins in size, antigenicity and/or amino acid sequence [38,39,69,86,87,88], depending on the technique used to analyse proteolysis. Complete degradation of SAA without fragments was observed following degradation by m∅ [13,38] and neutrophils [64] and was assigned to the activity of serine proteases [38,64]. Incomplete degradation by m∅ has also been attributed to serine proteases and elastase [38,39,69].…”
Section: Proteasesmentioning
confidence: 99%